An "essential herbal medicine"—licorice: A review of phytochemicals and its effects in combination preparations. (1st March 2020) - Jiang, Maoyuan; Zhao, Shengjia; Yang, Shasha; Lin, Xia; He, Xiguo; Wei, Xinyi; Song, Qin; Li, Rui; Fu, Chaomei; Zhang, Jinming; Zhang, Zhen
Abstract: Ethnopharmacological relevance: Licorice (Gancao in Chinese, GC), the dried root and rhizome of Glycyrrhiza uralensis Fisch., Glycyrrhiza inflata Bat. or Glycyrrhiza glabra L., is an "essential herbal medicine" in traditional Chinese medicine (TCM). There is a classic traditional Chinese medicine theory says that "nine out of ten formulas contain licorice" and licorice is considered as one of the most important herbal medicine which can reduce toxicity and increase efficacy of certain herbal medicine while it is combined application. In addition, it is a "medicine food homology" herbal medicine and also be widely used as a health food product and natural sweetener. However, no systematic literature review has been compiled to reveal its superiority. Herein, the aim of this work is to develop an overview of the state on phytochemicals, as well as effects of licorice in combination preparations, which can provide better understand the superiority of licorice and the special position in the application of TCM. Besides, ethnobotany, ethnopharmacological uses, quality control and toxicology of licorice have also been researched, which would provide reference for future clinical and basic research needs. Materials and methods: The information about licorice was collected from various sources including classic books about Chinese herbal medicine, and scientific databases including scientific journals, books, and pharmacopoeia. A total of 124 bibliographies, which are published from 1976 to 2019, have been searched and researched. Results: In this study, the interaction of chemical compounds between licorice and toxic herbal medicine, pharmacological effect of licorice, and the effect of licorice on pharmacokinetics of toxic compounds are considered as the main mechanisms underlying the effects of licorice in combination preparations. Besides, ethnobotany, ethnopharmacological uses and chemical constituents have been summarized. Conclusion: This work comprehensively reviews the state on ethnobotany, ethnopharmacological uses, phytochemicals, combined applications, quality control and toxicology of licorice. It will provide systematic insights into this ancient drug for further development and clinical use. Graphical abstract: Image 1